5 Effect of Species and Maturity on Winter Hardy Small Grain Silage Yield and Quality. (22nd October 2022) - Sartin, Abigail; Calus, Kallie; Hall, Alyssa; Grabau, Morgan; Redfearn, Daren; Drewnoski, Mary E
Abstract: Winter-hardy small grains offer an opportunity to improve soil health as a cover crop, and they can also be used as a forage source for cattle. Winter-hardy small grains differ in the time needed to reach various maturity stages. Species selection may also impact yield and nutritive value. A two-year study was conducted in eastern Nebraska to determine the effect of species and maturity on yield and nutritive value of winter-hardy small grains used for silage. Three species were evaluated; cereal rye, winter wheat, and winter triticale at four stages of maturity: boot, anthesis, milk, and soft dough. The experimental design was a randomized complete block design with four blocks per year. Small grain species were considered whole plots with maturity at harvest considered sub-plot. Each year, the small grain species were randomly assigned within each block. Within each plot, maturity was randomly assigned to one quarter of each plot. Dry matter (DM) forage yield, crude protein (CP), digestible organic matter (DOM), and nutrient yield per hectare were measured and analyzed using the mixed procedure of SAS. Forage yield increased for all species (P < 0.01) with maturity, except for wheat, where there was a decrease at soft dough. Forage yield of cereal rye and triticale did not differ (P>0.05), except at soft dough where triticale was greater (P < 0.01) than cereal rye. Forage yield of triticale and cereal rye yield was greater (P£0.05) than wheat at anthesis and soft dough. Crude protein (% DM) decreased (P < 0.01) with maturity across all species. Among species, CP for cereal rye was greater (P£0.01) than triticale at boot, anthesis, and soft dough, but not different (P³0.10) from wheat at boot, milk, and soft dough. At boot, anthesis, and milk stages, CP of triticale was not different (P³0.07) than wheat, but triticale was lower than wheat (P < 0.01) at soft dough. The DOM (% DM) decreased (P < 0.01) with maturity, except at soft dough. The DOM of cereal rye and wheat did not differ (P > 0.05), but both were greater (P < 0.01) than triticale. Cereal rye and triticale had greater (P £ 0.05) nutrient yields than wheat in terms of energy (DOM) and CP. There was no difference for CP yield across stages (P = 0.10), but there was an effect of maturity on DOM yield. The DOM yield increased from boot to anthesis, (P = 0.05), anthesis and milk did not differ (P = 0.08) and increased (P < 0.01) again at soft dough. This suggests that planting either cereal rye or triticale resulted in the greatest nutrient yield per acre. Harvest at anthesis had increased yield compared to boot with minimal loss in nutritive value; for maximizing energy yield per acre, harvesting at soft dough was the best option.